The effects of COVID-19 policies on livelihoods and food security of smallholder farm households in Nigeria: Descriptive results from a phone survey - Balana, Bedru; Oyeyemi, Motunrayo; Ogunniyi, Adebayo; Fasoranti, Adetunji; Edeh, Hyacinth O.; Aiki, Joel; Andam, Kwaw S. (International Food Policy Research Institute, 2020)
The Government’s policy measures such as travel restrictions, lockdowns, and restrictions on economic and social activities, aimed at curbing the spread of COVID-19, had affected the livelihoods and food security of smallholders in Nigeria. Using data collected from sample households from four Nigerian states, this study investigated the effects of COVID-19 pandemic policies on the incomes, employment, and food security situation of smallholder farming households. Results show that 88 percent of the households reported that they lost about 50 percent of their income due to the pandemic. As a result, about 66 percent of respondents reported they reduced food consumption. Travel and movement restrictions caused disruptions in agricultural activities and supply chains, as 29 percent of respondents reported planting fewer crops, 24 percent reduced cropping area, and 24 percent reduced fertilizer application. In terms of household’s food security, results show that COVID-19 significantly worsened the food security situation of many households in Nigeria, especially poorer households. More than 80 percent of respondents worried about not having enough food and 77 percent ate less food than they thought they should. Survey households also reported a significant reduction of consumption of proteins (eggs, meat, and dairy products) and fruits since the pandemic struck. Increases in food prices are felt by most households (85 percent). We suggest three key policy priorities: support vulnerable households to mitigate the impacts of income loss through cash transfer or improved credit access; interventions to improve agricultural inputs supply chains to ease the pandemic’s impact on agricultural production; and support food insecure households through direct food distribution.